L'essor des universités privées au Liban : stratégies de conquête de nouveaux « marchés » étudiants - Lama Kabbanji; Kévin Mary (Les éditions de la Maison des sciences de l'Homme, 2020)
Since 2005, in Lebanon, more than half of tertiary students are enrolled in a private institution. The Lebanese higher education system now appears stratified, consisting of a single public university, a few elite universities, and a myriad of private market-oriented universities, whose development began in the early 1990s and the development of economic policies of neo-liberal inspirations. This research examines the strategies put in place by these private universities to conquer new student «markets». We first analyze their spatial deployment through campus openings throughout the Lebanese territory whose goal is to look, ever further, new «clienteles» students. We develop here the idea of a new geography of higher education in Lebanon that has resulted in a relocation to the peripheries and urban margins, following the logic of academic capitalism. After the "confessional" fallback of universities during the war, the increase of geographic relocations to the peripheries here expresses the rise of a "student market" within the framework of the liberalization of the Lebanese economy, without dismantling the confessional lines of demarcation established by the war. We then discuss the competition that results from the establishment of these new institutions and the ways they try to respond by trying to stand out from each other. Finally, we are interested in the representations of which these universities are carriers and which refer to the search for international «labels» synonymous for them with a certain quality of teaching. These analyzes allow us to identify how the dominant neo-liberal model of higher education has been adapted in the Lebanese context.